Jawabanmu

2014-02-03T05:00:52+07:00
A. 6x + 5 = 26 - x 
    6x+x = 26-5
    7x = 21
      x = 3
b. 2 - 4x = 3
    2-3 = 4x
      -1 = 4x
       x = -1/4
c. x - 12 = 2x + 36
     x-2x = 36-12
       -1x = 24
d. -5x - 4x + 10 = 1
      -9x + 10 =1
       -9x=1-10
       -9x = -9
          x = 1
e. 2 + x/4 = 5
      x/4 = 5-2
       x/4 = 3
        x = 3/4
2014-02-03T09:19:29+07:00
A.) 6x + 5 = 26 - x
          7x = 21
            x = 3
b.) 2 - 4x = 3
           x = - 1/4
c.) x -12 = 2x + 36
          -x = 48
           x = - 48
d.) - 5x - 4x +10 = 1
                  - 9x = - 9
                      x = 1
e.) 2 + x/4 = 5
             x = 3/4